Predictors of cancer survivors' response to a community-based exercise program. (March 2020) - Brunet, Jennifer; Howell, Doris; Au, Darren; Jones, Jennifer M.; Bradley, Holly; Berlingeri, Antonia; Mina, Daniel Santa
Abstract: Objective: To explore the degree to which sociodemographic (i.e., age, sex, ethnicity, weight status, vocational status, marital status), medical (i.e., stage of cancer, treatment status, comorbidity burden), functional (i.e., self-rated health, exercise capacity), cognitive (i.e., exercise self-efficacy beliefs), and behavioural (i.e., program adherence, extra-curricular exercise) factors predicted cancer-related fatigue and quality of life among 224 cancer survivors who participated in the community-based Wellspring Cancer Exercise Program (WCEP). Design: Prospective, quasi-experimental single-group repeated measures design. Method: Data on predictors and outcomes were collected using self-report and objective measures upon enrollment in the program (week 0), every 10 weeks until program completion (weeks 10, 20, 30), and at 16-weeks follow-up (46 weeks). Data were analyzed using multilevel modeling. Results: In general, participants who were working or transitioning to work, rated their health better, and had higher exercise self-efficacy beliefs had lower cancer-related fatigue, and those who rated their health better and had higher exercise self-efficacy beliefs had higher quality of life. Also, there was a significant interaction between time and exercise self-efficacy beliefs for cancer-related fatigue and quality of life such that greater improvements were observed among participants with higher exercise self-efficacy beliefs. Conclusion: Cancer survivors' perceptions of their health and their ability to exercise should be fostered to ensure they respond positively to exercise programs in terms of cancer-related fatigue and quality of life. Highlights: There is variability in cancer survivors' response to community-based exercise programs. Exercise self-efficacy beliefs predict improvements in cancer-related fatigue and quality of life. Cancer survivors' perceptions of their health and their ability to exercise should be fostered.